Quality Assurance (QA) of Qualitative serological Tests in the Clinical Microbiology Laboratory: Limitations and Solutions - Zeeshan, Muhammad; Shaheen, N (Infectious Diseases Journal of Pakistan, 2022)
In a clinical microbiology laboratory, accurate and reliable results can only be achieved by adhering to quality assurance and quality control protocols. This process starts from patient’s sample collection, receiving, processing and final reporting. Method validation of each component is essential, and a breach may lead to faulty result. Due to high prevalence and rapid emergence of infectious diseases, the importance of rapid and reliable qualitative serological tests has increased. However, ignorance and noncompliance to quality assurance process by the laboratories, especially in low resource settings leads to inappropriate diagnosis which leads to wrong interpretation and hence inappropriate treatment and ultimately poor prognosis. Key words: Method validation, Quality assurance, Quality control